Brain Protection in Patients with Aortic Dissection and Coronary Artery Disease - Zhekov, Ihor I.; Kravchenko, Vitalii I.; Sarhosh, Oleh I.; Zinchenko, Genadii A.; Rudenko, Anatoliy V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To compare the effectiveness of methods of protecting the brain and visceral organs during operations for aortic aneurysms combined with coronary artery lesions. Materials and methods. In the period from 2012 to 2020, 23 patients with Stanford type A and non-A non-B aortic dissection with damage to the coronary arteries were operated at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine using the brain protection techniques. Out of 23 surgical interventions, 16 were performed for Stanford type A acute aortic dissection, 3 for Stanford type A chronic aortic dissection, 1 for Stanford type A subacute aortic dissection, and 3 for Stanford non-A non-B aortic dissection. The main causes of aortic dissection were hypertension (16 patients), Marfan syndrome (3 patients), bicuspid aortic valve (4 patients). Results. The most threatening postoperative complication in this group of patients is neurological damage, which was observed in 4 (17%) patients after surgery, with gradual recovery of brain function. Also, the complications observed were respiratory failure in 3 (13%) patients, which required long-term artificial ventilation (more than 72 hours), and multiple organ failure in 1 (4.3%) patient, which caused a fatal outcome.Complications such as kidney and liver failure were not observed (most likely due to the small sample size). Heart failure was not noted as well. Hospital mortality was 4.3% (1 fatal case). In our study, among the entire group of operated patients, symptoms of neurological damage occurred in 4 (17.4%) patients, hemorrhagic stroke was present in 1 (4.3%) patient with a complicated medical history, 2 (8.6%) patients had hemiparesis and in 1 case (4.3%) there were cognitive disorders. Conclusions. Comparing brain protection techniques, taking into account the prolongation of aortic clamping time due to coronary artery shunting compared to isolated aortic dissection, it can be concluded that longer duration of selective brain perfusion (retrograde or antegrade) or duration of circulatory arrest more often lead to postoperative complications, namely neurological lesions. On the other hand, the small number of observations does not make it possible to fully assess the impact of each of the techniques. Further follow-up with a larger sample will provide opportunities for a more complete evaluation of brain protection techniques in operations for dissecting aortic aneurysms and coronary artery lesions.